ON A CLASS OF SAKAGUCHI FUNCTIONS RELATED TO BERNOULLI LEMNISCATE AND MODIFIED SIGMOID FUNCTION - Olatunji, S.O; Dutta, H (TWMS journal of applied and engineering mathematics, 2020)
The aim of this investigation is to provide further results on a class of Sakaguchi functions related to Bernoulli Lemniscate and modified sigmoid function for the class [S.sub.L](s, t, [[PHI].sub.m],n). Early few coefficient bounds of f(z) together with sharp inequalities for the Fekete-Szego were obtained. Keywords: analytic functions, starlike functions, subordination, Sakaguchi functions, Bernoulli Lemniscate, modified sigmoid function, coefficient bounds. AMS Subject Classification: 30C45, 30C50